Prenatal exposure to antibiotics and the risk of orofacial clefts: a protocol for a systematic review and meta-analysis - Mahbubur Rahman; Md Shafiur Rahman; Kazunari Onishi; Md Mahfuzur Rahman; Abir Nagata; Takatoshi Nakagawa; Salma Sharmin (BMJ Open)
Introduction Orofacial clefts (OFCs), including cleft lip, cleft palate and combined cleft lip and palate, are among the most common craniofacial malformations in newborns and present significant healthcare challenges. Emerging evidence has raised concerns regarding the potential impact of prenatal exposure to antibiotics on fetal development. Antibiotics prescribed during pregnancy—particularly those that cross the placental barrier—may pose teratogenic risks. Previous studies investigating the association between prenatal antibiotic exposure and the risk of OFCs have yielded inconsistent results. However, no studies have yet attempted to summarise this evidence, highlighting the need for a comprehensive evaluation. This report describes a systematic review and meta-analysis protocol to retrospectively analyse the relationship between prenatal antibiotic exposure and the risk of developing OFCs, focusing on the role of antibiotic type and timing of exposure. The results of such a review will hopefully provide a comprehensive synthesis of the available evidence, helping to inform clinical practice and guide patient counselling regarding the use of antibiotics during pregnancy.Methods and analysis The planned systematic review and meta-analysis will adhere to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines to ensure a comprehensive and systematic approach to summarising the available evidence on the topic. This study will include longitudinal cohort studies, case–control studies, and interventional trials that investigate the association between prenatal antibiotic exposure and OFCs. The search strategy will cover major databases, including CINAHL, Cochrane Library, ClinicalTrials.gov, EMBASE, PubMed, Scopus and Web of Science, using tailored search terms. A team of independent assessors will screen article titles, abstracts and full texts. Any discrepancies will be resolved through discussions. Quality assessment will use the Newcastle-Ottawa Scale and Grading of Recommendations Assessment, Development and Evaluation criteria. Data extraction will focus on the study characteristics, participant details, exposure specifics and outcome measures. A random-effects meta-analysis will aggregate summary effect sizes, and heterogeneity will be assessed using I2 and Q statistics.Ethics and dissemination Ethical approval is not required for this systematic review, as it relies on already published data. The findings will be disseminated through peer-reviewed journals and conference presentations, providing critical insights into clinical practice and public health policies regarding antibiotic use during pregnancy.PROSPERO registration number CRD42024565064